FACTORS INFLUENCING THE DEMOGRAPHIC SITUATION IN EAST KAZAKHSTAN (Journal of Geography and Environmental Management, 2022)
Due to the global spread of the COVID-19 pandemic, our country, like many countries around the world, has also led to a deterioration in key demographic indicators: there has been an increase in mortality, migration has slowed or stopped, natural growth has decreased or the natural decline of the population has increased. In this paper, an attempt was made to evaluate the main components of demographic dynamics (birth rate, mortality,natural and migration movements) in 2020 within the framework of long-term trends in the development of the population, to determine the directions of influence of the pandemic on the processes of demography. Conclusions are drawn about the significant negative impact of the component of the coronavirus epidemic, which is considered a natural disaster in the system of geographical factors, on the death of the population, and forecasts are made about the possible impact on the birth rate. The demographic prospects of the territories under consideration are evaluated. In the article, an analysis of the migration processes of the population of the East Kazakhstan region was carried out, a step-by-step distribution of Population migration in the post-Soviet period was proposed and the factors of changes that occurred were identified. The purpose of the study is to study the factors of migration decline, the decrease in migration efficiency due to the strengthening of interregional socio-economic differences in the development of Regions and the uneven attractiveness of territories. In the article, an analysis of the migration processes of the population of the East Kazakhstan region was carried out, a step-by-step distribution of Population migration in the post-Soviet period was proposed and the factors of changes that occurred were identified.
Keywords: Keywords: population, natural movement, birth rate, mortality, migration, Kazakhstan, demographic policy, East Kazakhstan, covid-19 pandemic